Alrode train terminal: mobilising the invalid landscape - Grobbelaar, Jessica (My University, 2016)
In this dissertation I explore the notion of how space relates to human and place identity within the context of the buffer zones established under Apartheid. By exploring spaces remaining as political remnants the concept of the invalid landscape is investigated. Twenty-one years after the ! rst free elections these invalid landscapes still exist in South African cities, as open wounds on the democratic landscape. Historically divided communities remain residentially segregated facing each other uneasily across these buffer zones. This dissertation is a collage of theoretical and experimental discursions and case studies relating to identity, borders, and architecture. South Africa continues to grapple with myriad urgent practical problems while at the same time trying to de! ne a new national identity. Despite the gains of democracy, our nation is still faced with signi! cant challenges of which limited access to public transport remains a pressing urban issue. This thesis attempts to revalidate the spatial divide that continues to cleave the landscape of Alberton and Thokoza by proposing a train terminal that is in line with the vision of the National Development Plan of 2030. The project is focused on the translation and articulation of the landscape through an architectural language that is posited as an urban cicatrisation. By situating the proposed Alrode Train Terminal (ATT) within the invalid landscape, a bridge and operating connection between these two polarized communities is offered. An exploration of the idea of identity and the effects of the invalid landscape can take place while simultaneously addressing a practical challenge for our rapidly developing city. Inspiration for the project derives from the unprompted informal culture that has arisen within Johannesburg. Here life plays out alongside passing traffic made up of pedestrians, taxi ranks, streets,roadside activities and commerce. A social network aggregated by mobility where we see people starting anti-authoritarian movements, reclaiming and re-appropriating public space to meet their everyday needs. This de! ance of authoritarian space-making lays the groundwork for revalidating the invalid politically constructed landscapes. Traditional models of division are characterised by the vertical plane. The architecture of the ATT aims to collapse the vertical to put forward a new mediation of the horizontal plane and its architectural possibilities. The ATT acts as a bridge that affords its visitors the opportunity to transcend physical and cultural boundaries. By crossing between the polarized communities, visitors may potentially experience acculturation and in this way expand their identities
Document is submitted in partial fulfillment for the degree: Master of Architecture [Professional] at the University of the Witwatersrand, Johannesburg, South Africa, in the year 2016
Keywords: City planning--South Africa; Public spaces--South Africa